2012
DOI: 10.1007/s13762-012-0126-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance and genetic diversity in water-borne Enterobacteriaceae isolates from recreational and drinking water sources

Abstract: A total of 240 water-borne bacteria including 72 Escherichia coli, 83 Enterobacter, 30 Klebsiella, 36 Salmonella and 19 Shigella spp. isolates from drinking and recreational water sources were assessed for antibiotic resistance and genetic diversity. Escherichia coli (88.89 %) and species of Enterobacter (86.75 %), Klebsiella (83.33 %) and Salmonella (100 %) were resistant to cefadroxil, while [94 % Shigella spp. were resistant to cefaclor and cefuroxime. Ofloxacin was the most effective antibiotic against iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…A scoping report on “Antimicrobial Resistance in India” published by Department of Biotechnology, New Delhi, India in 2017 highlighted increasing load of antibiotic-resistant bacteria and ARGs in Indian surface waterbodies and major drinking water sources [ 54 ].Various other studies have also been undertaken across India to check for the presence of antibiotic-resistant bacteria in surface and groundwater sources [ 55 , 56 ]. These studies highlighted that the majority of rivers flowing in Bihar, Goa, Karnataka, Tamilnadu, Telangana states are contaminated with multidrug-resistant E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…A scoping report on “Antimicrobial Resistance in India” published by Department of Biotechnology, New Delhi, India in 2017 highlighted increasing load of antibiotic-resistant bacteria and ARGs in Indian surface waterbodies and major drinking water sources [ 54 ].Various other studies have also been undertaken across India to check for the presence of antibiotic-resistant bacteria in surface and groundwater sources [ 55 , 56 ]. These studies highlighted that the majority of rivers flowing in Bihar, Goa, Karnataka, Tamilnadu, Telangana states are contaminated with multidrug-resistant E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…1b). The Kirby-Bauer disk diffusion assay (Bauer et al, 1966) is used in both clinical and research settings (Felmingham and Brown, 2001) and has been widely used to characterize antibiotic resistance for environmental isolates (Sayah et al, 2005;Kumar et al, 2013;Zhang et al, 2014). Both EUCAST and CLSI have standardized protocols for disk diffusion methods.…”
Section: Agar Disk Diffusionmentioning
confidence: 99%
“…Enterobacter has a certain drug-resistance, 41 and further research was found that Enterobacter from drinking and recreational water sources exhibited varying antibiotic sensitivity. 42 Correspondingly, one Enterobacter strain was isolated with TC as the sole carbon substrate from the anode at the end of our experiment (Fig. S1 †).…”
Section: Bacterial Community Compositionmentioning
confidence: 96%